2017
DOI: 10.1055/s-0043-120918
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Cesarean Myomectomy: Is it a Safe Procedure?

Abstract: Objective Myomectomy performed during cesarean section is still controversial because of the potential for associated complications, especially with large myomas. Many obstetricians avoid performing cesarean myomectomy procedures because of the risk of uncontrollable hemorrhage. However, the prevalence of pregnant women with myomas is increasing, leading to an increase in the likelihood that physicians will encounter this issue. The aim of this study was to compare outcomes and complications of patients who ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
2
10
0
2
Order By: Relevance
“…In that study, they also evaluated 66 C/S myomectomy patients having myomas of 5 cm or more in diameter along with 31 non-myomectomy patients and reported that no differences were found between the C/S myomectomy group and the non-myomectomy group in terms of lowered hemoglobin levels, necessary blood transfusions or operation-related complication rates. [21] We achieved similar results in our study.…”
Section: Discussionsupporting
confidence: 88%
“…In that study, they also evaluated 66 C/S myomectomy patients having myomas of 5 cm or more in diameter along with 31 non-myomectomy patients and reported that no differences were found between the C/S myomectomy group and the non-myomectomy group in terms of lowered hemoglobin levels, necessary blood transfusions or operation-related complication rates. [21] We achieved similar results in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Conventionally, myomectomy is not recommended for those undergoing cesarean section as it may induce perioperative complications, especially the excessive hemorrhage that may involve an emergency hysterectomy [ 9 – 11 ]. In recent years, many studies indicated that myomectomy during cesarean delivery was safe and feasible [ 12 14 ]. We aim to investigate the safety and feasibility of cesarean myomectomy among pregnant women with uterine fibroids through analyzing the obstetric outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study [ 14 ], Kaymake et al reported no significant increase of bleeding risk and frequency of blood transfusion between the patients underwent cesarean myomectomy or cesarean section alone. In addition, Topcu et al [ 15 ] revealed the outcome variables (e.g., frequency of postoperative fever and mean duration of hospital stay) showed no significant difference between the cesarean myomectomy group and cesarean group.…”
Section: Discussionmentioning
confidence: 99%
“…Senturk et al also found control of bleeding by suturing the myoma bed and use of oxytocin but in some cases still uterine atony and bleeding occurred requiring hypogastric artery ligation. 7 We had used prophylactic B-Lynch sutures in all our patients. No atonic PPH occurred in any patient and none of them required hysterectomy.…”
Section: Discussionmentioning
confidence: 99%